Effect of ionic strength solution on the stability of chitosan-DNA nanoparticles - Picola, Isadora Pfeifer Dalla [UNESP]; Busson, Karen Andressa Nunes [UNESP]; Casé, Ana Helena [UNESP]; Nasário, Fábio Domingues [UNESP]; Tiera, Vera Aparecida de Oliveira [UNESP]; Taboga, Sebastião Roberto [UNESP]; Neto, João Ruggiero [UNESP]; Tiera, Marcio José [UNESP] (Taylor & Francis, 2013)
Chitosan-DNA nanoparticles employed in gene therapy protocols consist of a neutralised, stoichiometric core and a shell of the excess of chitosan which stabilises the particles against further coagulation. At low ionic strength, these nanoparticles possess a high stability; however, as the ionic strength increases, it weakens the electrostatic repulsion which can play a decisive part in the formation of highly aggregated particles. In this study, new results about the effect of ionic strength on the colloidal stability of chitosan-DNA nanoparticles were obtained by studying the interaction between chitosans of increasing molecular weights (5, 10, 16, 29, 57 and 150 kDa) and calf thymus DNA. The physicochemical properties of polyplexes were investigated by means of dynamic light scattering, static fluorescence spectroscopy, optic microscopy, transmission electronic microscopy and gel electrophoresis. After subsequent addition of salt to the nanoparticles solution, secondary aggregation increased the size of the polyplexes. The nanoparticles stability decreased drastically at the ionic strengths 150 and 500 mM, which caused the corresponding decrease in the thickness of the stabilising shell. The morphologies of chitosan/DNA nanoparticles at those ionic strengths were a mixture of large spherical aggregates, toroids and rods. The results indicated that to obtain stable chitosan-DNA nanoparticles, besides molecular weight and N/P ratio, it is quite important to control the ionic strength of the solution. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: chitosan; DNA; gene therapy; nanoparticles; Colloidal Stability; Effect of ionic strength; Electrostatic repulsion; Gel electrophoresis; Gene therapy protocols; Physicochemical property; Spherical aggregates; Transmission electronic microscopies; Aggregates; Chitosan; Electrophoresis; Fluorescence spectroscopy; Gene therapy; Molecular weight; Multilayers; Nanoparticles; Stability; Ionic strength; nanoparticle; sodium chloride; chemical interaction; drug stability; fluorescence spectroscopy; gel electrophoresis; ionic strength; light scattering; microscopy; particle size; physical chemistry; priority journal